PENGARUH MOTIVASI INTRINSIK, PENGETAHUAN KEWIRAUSAHAAN, DAN KEPRIBADIAN TERHADAP MINAT BERWIRAUSAHA PADA SISWA SMKN 12 SURABAYA - Iswandari, Asti (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2013)
The purposes of this study were to determine the effects of intrinsic motivation, entrepreneurial knowledge, and personality on student interest in entrepreneurship. Population of this study were students from grade XII of the 12th State Vocational School of Surabaya, for academic year 2012-2013 with total of 578 students. 236 samples were taken using proportional random sampling. Data were collected by questionnaires and documentations. This study was using quantitative analysis with multiple linear regression. The results showed that there are simultaneous effects between intrinsic motivation, entrepreneurial knowledge, and personality on student interest in entrepreneurship. Partially, there is an effect of intrinsic motivation and personality on student interest in entrepreneurship, whereas there is no effect of entrepreneurial knowledge on student interest in entrepreneurship.